2017
DOI: 10.1021/acsami.7b04841
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Electrodeposition of Nanocrystalline ZnxCo3–xO4 Films with High Activity and Stability for Electrocatalytic Oxygen Evolution

Abstract: The development of highly active, environmentally friendly, and long-term stable oxygen evolving catalysts at low costs is critical for efficient and scalable H production from water splitting. Here, we report a new and facile one-step electrodeposition of nanocrystalline spinel-type ZnCoO films from an alkaline Zn-Co-tartrate solution. The electrodeposited ZnCoO electrode could be directly used as the anode for the water electrolysis without any post treatment. The ZnCoO film shows a low and stable overpotent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…Han et al also reported the preparation of a nanocrystalline spineltype Zn x Co 3−x O 4 thin film using a one-step electrodeposition method. [130] Benefiting from the increased density of Co 3+ in octahedral sites induced by Zn 2+ , all the produced Zn−Co films exhibited better OER performance than a pure Co 3 O 4 film. Among the considered Zn/Co ratios, Zn 0.45 Co 2.55 O 4 exhibited the best performance with η = 330 mV at 10 mA cm −2 .…”
Section: Wwwadvenergymatdementioning
confidence: 96%
“…Han et al also reported the preparation of a nanocrystalline spineltype Zn x Co 3−x O 4 thin film using a one-step electrodeposition method. [130] Benefiting from the increased density of Co 3+ in octahedral sites induced by Zn 2+ , all the produced Zn−Co films exhibited better OER performance than a pure Co 3 O 4 film. Among the considered Zn/Co ratios, Zn 0.45 Co 2.55 O 4 exhibited the best performance with η = 330 mV at 10 mA cm −2 .…”
Section: Wwwadvenergymatdementioning
confidence: 96%
“…[61] The rate-determining step in the OER is the formation of CoOOH,w hich further forms CoO 2 through CoOOH + OH À !CoO 2 + H 2 O + e À . [23] The highly oxidized Co 4 + sites under OER conditions were observed by Favaroe tal. [62] through in operando photoelectron spectra and Zhang et al [63] through time-resolved FTIR spectroscopy;t hese authors proposedt hat increasing Co 4 + =Od ensity led to the creationo fa djacent oxo-bridged Co 4 + centers at which the concerted oxidation of water to molecular oxygen occurred with af ast turnover frequency (TOF).…”
Section: Resultsmentioning
confidence: 87%
“…The most widely accepted mechanism on transition‐metal oxides is known as the four‐electron‐transfer mechanism . The rate‐determining step in the OER is the formation of CoOOH, which further forms CoO 2 through CoOOH+OH − →CoO 2 +H 2 O+e − . The highly oxidized Co 4+ sites under OER conditions were observed by Favaro et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusion-limited current can only be exceeded (leading to OLC) if the preceding assumptions break down, by providing additional ions (via water splitting 11,51 or membrane discharge 22 ), activating new transport mechanisms (such as electro-osmotic instability, 9,11 surface conduction or electro-osmotic flow 12,13,16,31 ), or effectively shortening the diffusion length (by dendritic growth instability 33,34,49 ).…”
Section: Introductionmentioning
confidence: 99%